L4/5 accessibility for extreme lateral interbody fusion (XLIF): a radiological study - Quack, Valentin M. (Journal of orthopaedic surgery and research, 2022)
Potential advantages of the Extreme Lateral Interbody Fusion (XLIF) approach are smaller incisions, preserving anterior and posterior longitudinal ligaments, lower blood loss, shorter operative time, avoiding vascular and visceral complications, and shorter length of stay. We hypothesize that not every patient can be safely treated at the L4/5 level using the XLIF approach. The objective of this study was to radiographically (CT-scan) evaluate the accessibility of the L4/5 level using a lateral approach, considering defined safe working zones and taking into account the anatomy of the superior iliac crest. Hundred CT examinations of 34 female and 66 male patients were retrospectively evaluated. Disc height, lower vertebral endplate (sagittal and transversal), and psoas muscle diameter were quantified. Accessibility to intervertebral space L4/5 was investigated by simulating instrumentation in the transverse and sagittal planes using defined safe zones. The endplate L5 in the frontal plane considering defined safe zones in the sagittal and transverse plane (Zone IV) could be reached in 85 patients from the right and in 83 from the left side. Through psoas split, the safe zone could be reached through psoas zone II in 82 patients from the right and 91 patients from the left side. Access through psoas zone III could be performed in 28 patients from the right and 32 patients from the left side. Safe access and sufficient instrumentation of L4/5 through an extreme lateral approach could be performed in 76 patients of patients from the right and 70 patients from the left side. XLIF is not possible and safe in every patient at the L4/5 level. The angle of access for instrumentation, access of the intervertebral disc space, and accessibility of the safe zone should be taken into account. Preoperative imaging planning is important to identify patients who are not suitable for this procedure.
Gesehen am 23.09.2024